Profesionalisme dan Keterampilan Pustakawan - Hildawati Almah (Jurnal Adabiyah: Humanities and Islamic Studies, 2012)
It is undoubted that technological advancement has been dealing ith human necessity and influencing their life style, either in business, education, social, cultural, library, etc that force them to follow the rhythm of technological progress. Libaray one of educational supporting element closely deals with the technology. Therefore, librarians must be professional in doing their duty in line with technological advancement. To realize the professionalism, librarians are not only requested to provide some collections by using e-electonic, but, also increasing it through information networking. It certainly requires the skill of librarians to manage the library professionally.